Electrophysiological indices of response inhibition in human polydrug users. (September 2013) - Roberts, CA; Fairclough, S; Fisk, JE; Tames, FT; Montgomery, C
Previous research in ecstasy users suggests impairment of various executive functions. In general, the executive function of response inhibition appears unaffected by ecstasy use. Nonetheless, it remains a possibility that cognitive tasks alone are not sensitive enough to pick up subtle changes in function. The current study sought to investigate behavioural measures of response inhibition and their electrophysiological correlates in drug users. Twenty ecstasy polydrug users, 20 non-ecstasy polydrug users and 20 drug naïve controls were recruited. Participants completed questionnaires about their background drug use, sleep quality, fluid intelligence and mood state. Each individual also completed a Go/NoGo response inhibition task whilst electroencephalography (EEG) measures were recorded. Analysis of variance (ANOVA) revealed that there were no between-group differences on the behavioural measure of response inhibition. Multivariate analysis of variance (MANOVA) revealed no main effect of group across midline electrodes for the P3, N2 and P2 components. Univariate ANOVA revealed significant between-group differences in the P2 component with the ecstasy user group having a significantly higher mean amplitude than drug naïve controls at two midline frontal electrodes: at Fz and significantly higher mean amplitude than both control groups at FCz. The present study provides evidence of atypical early processing in ecstasy users that is suggestive of compensatory mechanisms ameliorating any behavioural differences.